Pleiotropic Effects of Glucocorticoids on the Immune System in Circadian Rhythm and Stress - Shimba, Akihiro; Ejima, Aki; Ikuta, Koichi (Frontiers in Immunology, 2021)
Glucocorticoids (GCs) are a class of steroid hormones secreted from the adrenal cortex. Their production is induced by circadian rhythms and stress. Importantly, GCs have various effects on immunity, metabolism, and cognition, including pleiotropic effects on the immune system. In general, GCs have strong anti-inflammatory and immunosuppressive effects. Indeed, they suppress inflammatory cytokine expression and cell-mediated immunity, leading to increased risks of infection and cancer. However, recent studies have shown that endogenous GCs induced by the diurnal cycle and dietary restriction enhance immune responses against infection and cancer by promoting the survival, redistribution, and response of T and B cells via cytokine and chemokine receptors. Furthermore, GCs enhance type 2 immunity and IL-17-associated immunity in stress conditions. Taken together, GCs have both immunoenhancing and immunosuppressive effects on the immune system.